The Effectiveness of Bibliocounseling Techniques as an Effort to Increase Students' Empathic Resilience in Preventing Cases of Bullying - Umaruddin Umaruddin; Ismail Tolla; Hamsu Abdul Gani (Universitas Negeri Malang, 2023)
The research aims to test the effectiveness of using bibliocounseling techniques in increasing student empathy in preventing bullying cases in junior high schools, using a quasi-experimental research design, pretest posttest one group design. The research subjects were five students who had low empathy criteria as measured using the student empathy scale. This research data collection method uses an empathy scale given at the beginning and end of treatment. Providing treatment using bibliocounseling in the form of short stories which in its application has several stages including: students are given time to read short stories, discuss the content of the story, reflect on themselves, develop commitment, try out commitment and reflect on experiences. Based on the results of the analysis, bibliocounseling using short stories is effective in increasing student empathy as an effort to prevent bullying cases in schools. This can be seen from the increase in scores at the end of the meeting. The pretest results from 5 people showed a minimum score of 60 and a maximum score of 66 with an average of 64. , standard deviation 2.455 after following treatment. The posttest results show a minimum score of 99 and a maximum score of 117 with a mean of 107.